Evolution of the views on the issues of the goals of marriage and their adaptation in the Catholic Church in relation to marriage rights and obligations - Bochen, Czesław (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Before the scope of the goals of marriage was defined, and hence the obligations and rights arising from the sacrament of marriage, for centuries there were feverish discussions concerning its properties. References were sought in not only the Old and New Testaments but also the views of Aristotle, Seneca and Plutarch were thoroughly explored. The theme of marriage, the meaning of virgin chastity and the rights attributed to marriage were discussed by early Christian thinkers, including Saint Methodius of Olympus, Saint Ambrose of Milan, Saint Jerome, Tertullian, Saint Augustine of Hippo, thus becoming a point of reference for further discussions (Hugh of Saint Victor, Peter Lombard, Peter Abelard, Stephen of Tournai, Isidore of Seville) or finally Saint Thomas Aquinas. The concept of Aquinas became the basis for the principle included in the 1917 edition of Canon Law Codex, where bearing and upbringing of offspring was set as priority. This is how Pius XI saw it(Casti connubi), but this point of view was subjected torevision during the period of so-called aggiornamento, as a result of which the Council Fathers abandoned the privilege of procreation, placing it on an equal level with „marital love” (Gaudium et spes). The 1982 edition of Canon Law Codex mentions two main marriage goals: giving birth to children and their educationas well as mutual help of spouses in realization of all good resulting from sacramental covenant. As practice has shown, it was even more difficult to determine marriage obligations. Canon Law Codexdid not define their scope, leaving this issue to legal theorists and jurisprudence. References were only sought based on three essential (and a fourth additional) matrimonial goods – unity, indissolubility, well-being of offspring and the marriage itself. There are no obligations that in the interests of the spouses’ welfare diminish value of the children, and the welfare of the children that wouldexclude the welfare of the parents. Both overlap in the implementation of the general good.